2010
DOI: 10.4028/www.scientific.net/msf.654-656.894
|View full text |Cite
|
Sign up to set email alerts
|

3D Transient Thermal Modelling and Experimental Validation of the Temperature Distribution during Laser Heating of Ti6Al4V Alloy

Abstract: Abstract.A three 3D transient finite element model has been developed to predict the temperature distribution in Ti6Al4V alloy plate workpiece. It is found that the temperature profile is strongly dependent on the parameters of the laser beam and material properties. Also the thermal model results were compared with results produced by experimental work and these show close agreement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The use of diffractive optics for laser beam shaping provides us with an opportunity to obtain specified properties of processed materials. Investigations of the thermal state of the surface layers of materials subjected to laser irradiation, carried out in [55][56][57][58][59]64], showed that the characteristics of the temperature field in materials (i.e., the magnitude and gradient of temperatures and the rate of heating and cooling) are largely influenced by the energy parameters of the irradiation, the movement speed of the energy source, the nature of the power distribution in the beam, the thermophysical characteristics, and the geometric dimensions of the processed material. The temperature gradient in the surface layer under laser irradiation on large parts is high, reaching the value of 10 8 -10 9 K/m, and gradually decreases from the surface into the depth of the material [106].…”
Section: Discussion Of the Presented Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of diffractive optics for laser beam shaping provides us with an opportunity to obtain specified properties of processed materials. Investigations of the thermal state of the surface layers of materials subjected to laser irradiation, carried out in [55][56][57][58][59]64], showed that the characteristics of the temperature field in materials (i.e., the magnitude and gradient of temperatures and the rate of heating and cooling) are largely influenced by the energy parameters of the irradiation, the movement speed of the energy source, the nature of the power distribution in the beam, the thermophysical characteristics, and the geometric dimensions of the processed material. The temperature gradient in the surface layer under laser irradiation on large parts is high, reaching the value of 10 8 -10 9 K/m, and gradually decreases from the surface into the depth of the material [106].…”
Section: Discussion Of the Presented Resultsmentioning
confidence: 99%
“…The study of thermal processes allows us to identify common relations and the main areas for the improvement of processes to initiate concentrated energy flows. Lasers' effects on opaque materials in a wide range of power densities, of up to 10 13 W/m 2 , are satisfactorily described by the thermal model [56,57]. Material properties depend on the thermal state.…”
Section: Calculation Of the Power Density Distribution Of The Laser Beam To Create A Desired Thermal Effect In Materialsmentioning
confidence: 99%